Canada : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that the Canadian economy has slowed substantially since late 2000. The slowdown in large part has reflected the slowing in the United States economy, which has reduced growth in Canada's exports and contributed to weakening private investment. In addition, consumption growth has moderated, owing to a slowing in real income growth, a softening in the employment situation, and an associated fall in consumer confidence. The slowing in economic activity in recent quarters has also led to a decline in resource utilization.